SARS-CoV-2 the Cause of the Pandemic (Turkey Health Literacy Journal, 2020)
Coronaviruses are RNA viruses that have a large number of natural hosts and they affect more than one system. In humans, they can cause clinical illnesses that range from the common cold to more severe respiratory illnesses such as SARS and MERS. The recently emerged SARS-CoV-2 has caused disease in China and subsequently caused a worldwide pandemic. Although prevention and treatment efforts still continue, it causes critical cases and deaths all over the world. The virus was recognized with severe acute respiratory syndrome coronavirus by International Virus Classification Committee (ICTV) this virus is referred to as acute syndrome coronavirus 2 (SARS-CoV-2), and as this virus was detected with SARS-CoVs. The next step in pursuing control of the COVID-19 outbreak should focus on screening, identification, isolation and characterization of CoVs found in wildlife species, particularly bats. Animal models suitable for research in vitro as well as in vivo should be presented.